EFFICIENCY AND ADVANTAGES OF SUMMATIVE ASSESSMENT AS A FACTOR IN IMPROVING THE QUALITY OF EDUCATION - Amanbaev, Muratbay Abdimuratovich; Eshanova, Sapura Tazabaevna (SCIENCE and SOCIETY, 2026)
This article examines the role of summative assessment in the educational process and its contribution to improving educational quality. The theoretical foundations, international experience, and practical significance of summative assessment are analyzed. The findings indicate that summative assessment is an effective mechanism for measuring learning outcomes, ensuring educational accountability, and improving educational quality.
Keywords: summative assessment; educational quality; assessment; learning outcomes; educational effectiveness